Investigating the Circadian Regulation of the Inner Blood Retinal Barrier in Early and Intermediate Age-Related Macular Degeneration - Naylor, Aisling (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2021)
Age-related macular degeneration (AMD) is the leading cause of central visual impairment worldwide. It is a multifactorial condition leading to the painless, progressive loss of central vision. There are currently no treatments available for geographic atrophy (GA), the advanced stage of dry AMD. Hudson et al., 2019 demonstrated that the gene CDLN-5 is regulated by BMAL1 and the circadian clock. CDLN-5 encodes for claudin-5, one of the most enriched tight junction proteins in the inner blood retinal barrier (iBRB). Fundus fluorescein angiography (FFA) in healthy human subjects demonstrated an increased permeability of the iBRB in the evening compared to the morning. Overall, these findings suggest that there may be an inner-retina derived component in the early pathophysiological changes associated with AMD and directly implicates claudin-5 as a key mediator of subsequent RPE pathology. To continue the clinical portion of this research, we are making a full assessment of circadian iBRB regulation in patients with defined degrees of dry AMD and age-matched controls. We have performed quantitative FFA and optical coherence tomography (OCT) in the morning and the evening in the same individual to assess retinal blood vessel integrity and retinal thickness changes. We have also screened participants? blood samples at both timepoints to correlate any potential changes in inflammatory status, melatonin and cortisol levels and circadian mediated changes in clock components with barrier integrity at particular times of day. In addition, participants will have DNA isolated and subsequently genotyped for AMD risk variants to determine if there is a link between severity of disease, risk variant and changes in iBRB integrity or vessel permeability. In gaining an understanding of circadian regulation of the iBRB in a clinical setting in human subjects, we will be positioned to make profound conclusions on its role in AMD pathophysiology, aiding our understanding of GA pathophysiology and potentially, in the future, development of therapeutic strategies to treat the condition.
APPROVED
Keywords: AMD; Claudin-5; Blood Retina Barrier; Circadian; Age-Related Macular Degeneration; Geographic Atrophy; FFA; Fundus Fluorescein Angiography; Inner Blood Retina Barrier; iBRB; BRB